Go for gold inspiration to increase your leadership impact - Maxwell, John C. (Thomas Nelson, 2008)
If you've read any of John C. Maxwell's books on leadership, you know that leadership is developed daily, not in a day. That's why he's created Go for Gold, a daily companion to Leadership Gold. It's designed to help supercharge your growth as a leader. Go for Gold offers daily bite-sized leadership lessons taken from Dr. Maxwell's catalog of leadership and personal development books. Organized into twenty-six weekly lessons with space for notes from your own leadership journey, Go for Gold will help you jump-start your leadership growth with wisdom and best practices from John C. Maxwell.